Dis/connectivity in the South Caucasus : imaginaries, the effects of power, ambivalences - Smolnik, Franziska (2023)
Zusammenfassung: Connectivity, especially in the transport sector, has become a ubiquitous issue in the South Caucasus in recent years. Transport connectivity also plays a central role in the European Union’s policy towards the region. As part of its Global Gateway Initiative, the EU has made a commitment that is both value-based and geostrategic. To do justice to this commitment, the EU should consider the different dimensions of transport connectivity and their implications on several levels and in an integrated manner. In particular, the EU should take into account the link between connectivity and questions of political power. The EU could provide support in establishing genuinely inclusive and transparent multi-stakeholder processes and independent project monitoring. This could point the way towards a more holistic approach to connectivity. The EU should also critically examine its commitment to connectivity for possible conflicts of objectives. The policy debate in Berlin and Brussels would benefit from a more intensive exchange with critical logistics, infrastructure and connectivity studies. Their findings could contribute to a more nuanced view of transport connectivity and its complexities and ambivalences